Catalyst for the oxychlorination of ethylene to 1,2-dichloroethane and its preparation method
A catalyst composition with copper, magnesium, and zirconium on alumina supports addresses temperature control and agglomeration issues in 1,2-dichloroethane production, achieving high conversion and purity with reduced by-products.
Patent Information
- Application Number
- JP2024542148
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-19
- Filing Date
- 2023-01-19
- Publication Date
- 2025-01-24
AI Technical Summary
Existing methods for producing 1,2-dichloroethane face challenges such as difficulty in temperature control in fixed bed reactors due to hot spots, catalyst agglomeration in fluidized beds, and high production of undesirable chlorinated by-products, leading to reduced efficiency and product quality.
A catalyst composition comprising copper, magnesium, and zirconium compounds supported on a high surface area alumina carrier, designed for fluidized bed reactors, which enhances ethylene conversion, selectivity, and purity of 1,2-dichloroethane while minimizing by-product formation.
The catalyst achieves high ethylene conversion rates with improved selectivity and purity of 1,2-dichloroethane, reduces catalyst agglomeration, and lowers the production of chlorinated by-products, thereby enhancing product quality and operational stability.
Smart Images

Figure 2025502309000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims priority to U.S. Provisional Patent Application No. 63 / 300,870, filed January 19, 2022, which is incorporated by reference in its entirety.
[0002] The present disclosure generally relates to catalysts for the oxychlorination of ethylene to 1,2-dichloroethane (DCE) that can provide high ethylene conversion, high dichloroethane selectivity, and high DCE crude purity. The present disclosure also relates to methods for preparing such catalysts. [Background technology]
[0003] The most common method for producing 1,2-dichloroethane is the oxychlorination of ethylene, in which ethylene is converted with hydrochloric acid (HCl) and oxygen (or an oxygen-containing gas) to produce 1,2-dichloroethane and water. For this reaction, fixed-bed and fluidized-bed processes have been developed and are currently in use. Various processes based on this reaction are carried out using oxygen-enriched gases such as air or more or less pure oxygen. The latter can contain small amounts of impurities, e.g. Ar, N2, CO, CO2, etc.
[0004] In processes using fixed bed reactors, the temperature control of the fixed bed is difficult due to the presence of localized hot spots in the tubes. In processes using fluidized bed oxychlorination reactors, the use of certain catalysts in the reactors can cause the catalyst to stick, especially at relatively low temperatures or high HCl partial pressures, which can result in agglomeration of catalyst particles, loss of catalyst fluidity, and clogging of cyclones. Summary of the Invention [Problem to be solved by the invention]
[0005] It is an object of the present invention to provide a catalyst for the oxychlorination of ethylene to DCE, which provides high activity (allowing low reaction temperatures), excellent DCE selectivity, and especially high DCE crude purity (low selectivity to undesired chlorinated by-products).When such a catalyst is used in powder form in a fluidized bed process, a further object is that the catalyst can be operated under industrial conditions with minimal risk of sticking. [Means for solving the problem]
[0006] According to an embodiment, described herein is a catalyst composition including a support and a catalytic metal compound on the support. The catalytic metal compound can include a copper compound; and a zirconium compound, and the support is about 50 m. 2 / g ~ approx. 250m 2 / g BET surface area.
[0007] According to further embodiments, described herein is a method for preparing a zirconia-based zirconia solubility salt comprising the steps of: dissolving (a) a copper compound and (b) a zirconium compound in a solvent at a temperature between about 20° C. and about 80° C. with stirring to form a solution; 2 / g ~ approx. 250m 2 3. A method for preparing a catalyst composition comprising the steps of: applying a catalyst composition onto a support having a BET surface area of 100 nm to 100 nm / g, wherein the support is rotated at about 50 revolutions per minute (rpm) to about 150 rpm; and drying the coated support at a temperature of about 75° C. to about 180° C. for about 1 hour to about 20 hours to remove free water. [Brief description of the drawings]
[0008] The drawings described below are for illustrative purposes and are not intended to limit the scope of the present disclosure in any way. [Figure 1] FIG. 1 is a chart showing the DCE selectivity of catalysts according to the invention (Examples 1-5) versus comparative catalysts (Comparative Examples 1-4) when measured at temperatures of about 220-240° C. [Diagram 2]FIG. 2 is a chart showing the selectivity to chlorine by-products for catalysts according to the invention (Examples 1-5) versus comparative catalysts (Comparative Examples 1-4) when measured at temperatures of about 220-240° C. [Diagram 3] FIG. 3 is a chart showing the DCE purity of catalysts according to the invention (Examples 1-5) versus comparative catalysts (Comparative Examples 1-4) as measured at temperatures of about 220-240° C. [Figure 4] FIG. 4 is a chart showing ethylene conversion of catalysts according to the invention (Examples 1-5) versus comparative catalysts (Comparative Examples 1-4) when measured at temperatures between about 220-240° C. [Diagram 5] FIG. 5 is a chart showing the hydrochloric acid conversion of catalysts according to the invention (Examples 1-5) versus comparative catalysts (Comparative Examples 1-4) when measured at temperatures of about 220-240° C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Described herein is a catalyst composition for use in the oxychlorination of ethylene to 1,2-dichloroethane (DCE) and a method for its preparation. According to an embodiment, the catalyst composition comprises a copper compound, an alkaline earth metal compound comprising magnesium, and a transition metal compound comprising zirconium. Surprisingly, it has been found that it is possible to obtain a catalyst for the oxychlorination of ethylene to DCE, which is capable of improving the purity of the DCE product due to the reduced selectivity towards chlorinated by-products at high ethylene conversions.
[0010] When air is used as the oxygen-containing gas, industrial processes are often operated in a single pass mode, with no recycle stream sending a portion of the reactor effluent to the reactor inlet. In that case, when air is used, ethylene and hydrogen chloride are usually fed to the reactor in a nearly stoichiometric ratio, allowing for nearly complete conversion of both ethylene and hydrogen chloride. In practice, ethylene is usually fed in slight excess to minimize the unconverted hydrogen chloride level in the reactor effluent. When more or less pure oxygen is used as the oxygen-containing gas, the ethylene and hydrogen chloride ratios are generally fed to the reactor very differently. Typically, ethylene is fed in large excess, resulting in nearly complete conversion of hydrogen chloride, while ethylene is only partially converted. After separation of EDC, hydrogen chloride, some water and by-products, the remaining gas stream after removal of the purge stream is recycled to the reactor. In this recycle process, the conversion of ethylene per pass is usually kept fairly low (e.g., less than about 90% to less than about 96%).
[0011] The catalysts used in the oxychlorination process may contain copper chloride as an active ingredient. To improve activity, selectivity and / or operability, further promoters can be introduced into the catalyst formulation. The most commonly used are magnesium chloride, potassium chloride, cesium chloride and / or rare earth chlorides. The active copper species and promoters can be deposited on a high surface area support such as diatomaceous earth, clay, fuller's earth, silica or alumina. Generally, the copper and promoters are impregnated into the support by a solution containing all metals in the chloride form. In some cases, the components are coprecipitated with the support.
[0012] In a fixed bed reactor, the catalyst is packed into vertical alloy tubes held by upper and lower tube sheets. Fixed bed catalysts are usually in the form of small pellets, granules, cylinders, or hollow cylinders (rings). It is important to pack the catalyst evenly into the tubes to ensure uniform pressure drop, flow, and residence time in each tube. The shape and size of the suitable catalyst vary depending on the reactor used. However, temperature control remains difficult in fixed beds due to localized hot spots in the tubes.
[0013] To minimize the formation of hot spots, an inert diluent is mixed with the catalyst pellets in different proportions along the length of the tube to achieve low catalytic activity at the inlet and maximum catalytic activity at the outlet. Alternatively, the tube is loaded with catalysts having increasing loadings of copper compound to create an activity gradient along the length of the tube.
[0014] Fixed-bed oxychlorination also uses multiple reactors connected in series, primarily to control heat release by staging the air or oxygen feed. Each successive reactor may contain catalyst with an increasingly higher copper chloride loading. Fixed-bed oxychlorination is generally operated at higher temperatures (230-300°C) and gauge pressures (150-1400 kPa). Fixed-bed reactors have a limited catalyst life due to fouling or coking of the catalyst bed, necessitating periodic complete catalyst replacement.
[0015] Fluidized bed oxychlorination reactors are typically vertical cylindrical vessels with a support grid and feed sparger system designed to provide good fluidization and feed distribution. The fluidized bed catalyst is a fine powder having a particle size ranging from about 20 microns to about 200 microns. During operation, catalyst carryover is recovered in internal or external cyclones and the heat of reaction is removed by internal cooling coils.
[0016] Compared to fixed-bed processes, fluidized beds have improved transport properties, resulting in uniform temperature distribution throughout the reactor and allowing operation at lower pressures and temperatures. Typical operating temperatures and gauge pressures for fluidized bed reactors are 220-245°C and 150-500 kPa, respectively. Commercially available fluidized bed reactors can be operated at 99.5-99.8% HCl conversion. Selectivity to 1,2-dichloroethane is typically 96-97.5%.
[0017] In contrast to fixed bed reactors, fluidized bed reactors using some catalysts can suffer from catalyst sticking, especially at relatively low temperatures or high hydrochloric acid partial pressures, resulting in agglomeration of catalyst particles, loss of catalyst fluidity, and plugged cyclones. Such catalyst sticking must be avoided by all means, since it causes great economic damage to the production plant. Catalyst sticking is caused by improper operating conditions or the properties of the catalyst itself. The addition of alkali metals and / or alkaline earth metals, such as potassium and magnesium, to the catalytic agent is known to improve the resistance to catalyst sticking.
[0018] The by-products produced in the oxychlorination process are carbon oxides (CO+CO2) and chlorinated hydrocarbons. Of these chlorinated by-products, 1,1,2-trichloroethane, cholor, ethyl chloride, chloroform, and carbon tetrachloride are the most common. In general, the selectivity to carbon oxides and chlorinated by-products increases as the operating temperature increases. Since all by-products lead to reduced ethylene efficiency, selectivity to these by-products in the oxychlorination of ethylene must be minimized. CO and CO2 are easily separated from the DCE product and therefore do not adversely affect the product quality, whereas the heavily chlorinated organic by-products are not easily separated. These heavily chlorinated organic by-products can be harmful and, if present in the DCE product, will reduce the quality and value of the DCE product.
[0019] It is to be understood that the invention is not limited to the details of construction or process steps set forth in the following description, as the invention is capable of other embodiments and of being practiced or of being carried out in various ways.
[0020] References throughout this specification to "one embodiment," "a particular embodiment," "one or more embodiments," or "an embodiment" mean that a particular feature, structure, material, or characteristic described in connection with an embodiment is included in at least one embodiment of the invention. Thus, the appearances of the phrases "in one or more embodiments," "in a particular embodiment," "in one embodiment," or "in an embodiment" in various places throughout this specification are not necessarily all referring to the same embodiment of the invention. Furthermore, the particular features, structures, materials, or characteristics may be combined in any suitable manner in one or more embodiments.
[0021] As used herein, the singular forms "a," "an," and "the" include plural references unless the context clearly dictates otherwise. Thus, for example, reference to a "catalytic material" includes not only a single catalytic material but also a mixture of two or more different catalytic materials.
[0022] As used herein, the term "about" in connection with a measured quantity refers to normal variation in that measured quantity that would be expected when one of ordinary skill in the art makes the measurement and exercises a level of care commensurate with the purpose of the measurement and the precision of the measurement device. In certain embodiments, the term "about" includes the stated numerical value ±±10%, e.g., "about 10" includes 9 to 11.
[0023] The term "at least about" in relation to a measured quantity refers to normal variations in the measured quantity and higher amounts that would be expected when one of skill in the art makes the measurement and exercises a level of care commensurate with the purpose of the measurement and the precision of the measurement device. In certain embodiments, the term "at least about" includes the stated number minus 10% and higher, e.g., "at least about 10" includes 9 and greater than 9. The term can also be expressed as "about 10 or greater." Similarly, the term "less than about" typically includes the stated number plus 10% and lower amounts, e.g., "less than about 10" includes 11 and less than 11. The term can also be expressed as "less than about 10."
[0024] Unless otherwise stated, all parts and percentages are by weight. Weight percent (wt %) is based on the total composition unless otherwise stated.
[0025] Although the disclosure in this specification refers to specific embodiments, it should be understood that these embodiments are merely illustrative of the principles and applications of the present invention. It will be apparent to those skilled in the art that various modifications and variations can be made to the compositions and methods without departing from the spirit and scope of the present invention. Therefore, it is intended that the present invention cover modifications and variations that come within the scope of the appended claims and their equivalents.
[0026] catalyst composition The catalyst compositions described herein achieve high ethylene and HCl conversion while improving DCE selectivity and product purity. In particular, the amount of undesirable heavy chlorinated by-products is reduced, improving product quality and value while reducing refining costs and protecting the environment. In some embodiments, the catalyst compositions according to embodiments herein have an ethylene dichloride selectivity of about 95 mol % to about 99.9 mol % when contacted with hydrochloric acid, ethylene and oxygen at a temperature of about 200° C. to about 250° C.
[0027] According to one or more embodiments, the catalyst composition described herein uses a support material. In the case of a fluidized bed catalyst, the metal can be deposited on a support, such as a high surface area support. One of the reasons for using a high surface area support is that the metal can be distributed over a large area, thereby reducing catalyst sticking.
[0028] Examples of high surface area supports include, but are not limited to, silica, magnesia, diatomaceous earth, clay, fuller's earth, alumina, zeolite, or combinations thereof. According to one or more embodiments, the support may be, for example, a high surface area powder (e.g., gamma, delta, or theta alumina powder) including particles, granules, and / or spheres (e.g., alumina microspheres or nanospheres in amorphous or colloidal form) suitable for flowable support, referred to herein as "support". In embodiments, the alumina support may be an activated alumina or transition alumina produced by calcination of hydrated or hydroxylated precursor alumina. These activated aluminas may be identified by an ordered structure observable by X-ray diffraction patterns, which indicates a mixed phase material with minimal or no low surface area or crystalline phase alpha alumina. In some embodiments, the support may be in a form suitable for fixed bed reactors, and may be in the form of tablets and / or extrudates. For example, tablets or extrudates may be formed of compressed or extruded particles, granules, and / or spheres, as described above. The tablets and / or extrudates can have a cross-sectional dimension of from about 1 mm to about 100 mm, or any suitable value or subrange within this range.
[0029] Alpha alumina is identified by its crystalline phase defined by X-ray diffraction. High surface area activated aluminas are often defined as transition aluminas, but the phase transition may be a continuum with varying percentages of multiple mixed phases, such as, but not limited to, gamma, delta and theta phases, based on the calcination temperature selected to achieve the desired support surface area. According to embodiments, a gamma alumina support may be used. In embodiments, the gamma alumina support is at least about 95%, or at least about 98%, or at least about 99%, or at least about 99.995% gamma phase and at least about 50% alpha alumina. 2 / g ~ approx. 250m 2 / g, or about 70m 2 / g ~ approx. 225m 2 / g, or about 100m 2 / g ~ approx. 215m 2 / g, or about 150m 2 / g ~ approx. 205m 2 According to an embodiment, the support (e.g., gamma alumina powder) has a surface area of at least about 80 m to adequately distribute the metal load and reduce the tendency for sticking. 2 The catalyst is described below in terms of a fluidizable alumina support (e.g., gamma alumina powder) for purposes of illustration and not limitation.
[0030] According to an embodiment, the alumina support material has a density of about 0.5 g / cm 3 ~Approx. 4.0g / cm 3 , or about 0.75 g / cm 3 ~About 3.0g / cm 3 , or about 1.0 g / cm 3 ~Approx. 2.0g / cm 3 , or about 0.7 g / cm 3 ~Approx. 1.3g / cm 3 , or about 3.65 g / cm 3 The fluidizable alumina support material has a compacted bulk density of about 0.1 cm 3 / g ~ approx. 2cm 3 / g, or about 0.2 cm 3 / g ~ approx. 1cm 3 / g, or about 0.3 cm3 / g ~ approx. 0.75cm 3 / g pore volume. According to embodiments, the fluidizable alumina support material may have a particle size distribution in which (a) about 90 to about 100 volume percent of the particles have a diameter less than about 150 μm, or less than about 140 μm, or less than about 125 μm, or less than about 110 μm; (b) about 50 to about 60 volume percent of the particles have a diameter less than about 75 μm, or less than about 70 μm, or less than about 65 μm, or less than about 60 μm; and (c) about 20 to about 35 volume percent of the particles have a diameter less than about 45 μm, or less than about 40 μm, or less than about 35 μm, or less than about 30 μm. Particle size distribution is measured by a Fraunhofer laser diffraction (light scattering) analyzer from Malvern Instruments, Ltd., where a 5 g sample of the material is dispersed in 100 mL of deionized water for 1 minute using a magnetic stirrer at room temperature (about 20°C to about 25°C) and atmospheric pressure (about 1 atm) to form a suspension, and 4 mL of the suspension is diluted with 130 mL of deionized water and analyzed using the analyzer at 2500 rpm (room temperature and atmospheric pressure). Such alumina support materials are easily fluidizable, relatively stable, mechanically strong, and resistant to wear. Aluminas useful as supports are, for example, Sasol products Puralox® SCCa-57 / 170 and Catalox® SCCa-25 / 200 high purity activated aluminas.
[0031] Additionally, the alumina support may be stabilized by any means known in the art to prevent undesirable changes in the activated alumina phase after the finished catalyst is put into use. Examples of such stabilizing components include, but are not limited to, lanthanum (La), praseodymium (Pr), cerium (Ce), silicon (Si), and the like, as minor components dispersed throughout the alumina support prior to impregnation with the active catalyst formulation. For example, the alumina support may include about 0.005% to about 0.50% by weight of one or more stabilizing components, or any individual value or subrange therein.
[0032] It is recognized that some alumina support materials may contain, in addition to aluminum oxide (Al2O3), small amounts of impurities of other metals such as metal oxides, e.g., less than about 0.02 wt.% sodium oxide, less than about 0.05 wt.% iron oxide (Fe2O3), less than about 0.3 wt.% titanium dioxide, less than about 0.2 wt.% silicon dioxide, etc. Ti compounds may unintentionally remain in the alumina from the alumina manufacturing process without significantly affecting the physicochemical properties of the alumina. In some embodiments, the support is free or substantially free of titanium, e.g., the support may contain less than 1500 ppm (by weight), less than 1000 ppm, less than 500 ppm, or 0 ppm titanium, or any individual value or subrange within these ranges.
[0033] In some embodiments, the catalyst composition is free or substantially free of silica. For example, in some embodiments, the support is free of silica and / or the composition is free of silica as a whole, or contains less than 500 ppm, less than 400 ppm, less than 300 ppm, less than 200 ppm, less than 100 ppm by weight of silica, or any individual value or subrange within these ranges. Without being bound to a particular theory, it is believed that silica may reduce the activity of the catalyst in the oxychlorination of ethylene to dichloroethane.
[0034] In some embodiments, the support is not activated and / or does not include activated alumina. For example, prior to impregnation and / or adsorption of the catalytic metal, the support is not heated to an elevated temperature, such as a temperature exceeding about 100°C, about 200°C, about 300°C, about 400°C, about 500°C, about 600°C, about 700°C, about 1000°C, or about 600°C to about 1200°C, or any individual value or subrange therein. Without being bound to a particular theory, it is believed that pre-heating the support at an elevated temperature can reduce the BET surface area of the support by about 25% to about 75%, for example, by sintering and phase transformation. Such reduction in the surface area of the support can affect the performance of the catalyst in the conversion of ethylene to dichloroethane by an oxychlorination process.
[0035] Without being bound by any particular theory, it is believed that only certain ranges of loadings of at least one transition metal, including Cu and Zr, result in all of the high performance characteristics described above. Outside of certain loading ranges of active metals, high performance may not be achieved in all respects. For example, increasing Cu content improves catalytic activity but makes the catalyst more susceptible to sticking. Increasing Mg content makes the catalyst less susceptible to sticking, but additional Mg reduces catalytic activity and DCE crude purity. Increasing Zr content makes the catalyst less susceptible to sticking and also increases DCE crude purity, but reduces catalytic activity slightly. Metal loadings outside the disclosed ranges result in reduced catalytic performance in one or more properties, including catalytic activity (i.e., ethylene and HCl conversion), catalyst selectivity, DCE product purity, and / or sticking. According to embodiments, the catalysts described herein, when employed in a process for the oxychlorination of ethylene in an air-based fluidized bed reactor, without effluent recycle, provide a crude dichloroethane purity of from about 99.20% to about 99.90% by weight, or any individual value or subrange within this range.
[0036] The copper compound is used in the form of a water-soluble salt and can be used in the form of copper chloride. However, other copper salts that can be converted to chloride during the oxychlorination process can also be used, such as other halide salts, such as nitrates, carbonates, sulfates, or bromides. The copper salt is deposited on the alumina support using the same techniques as described above. The amount of copper metal deposited is determined based on the desired activity and the specific fluidization characteristics of the support for the fluidized bed catalyst application.
[0037] According to embodiments herein, the catalyst as described may include about 1% to about 10% by weight copper metal, or any individual value or subrange within this range, based on the total weight of the catalyst composition. In embodiments, the copper salt is copper chloride (e.g., copper II chloride). The minimum amount of copper metal may be about 2.0% by weight, or about 3.0% by weight, based on the total weight of the catalyst, or any individual value or subrange within this range. The maximum amount of copper metal may be about 6.0% by weight, about 8.0% by weight, about 10% by weight, or any individual value or subrange within this range, based on the total weight of the catalyst.
[0038] The at least one alkaline earth metal compound comprises magnesium and may comprise additional alkaline earth metals, such as calcium, strontium, barium, or mixtures thereof. In one or more embodiments, the at least one alkaline earth metal compound comprises magnesium and contains no or only trace amounts (e.g., less than 1 ppm) of other alkaline earth metals / compounds. The at least one alkaline earth metal is used in the form of a water-soluble salt and may be used in the form of an alkaline earth metal chloride. However, other alkaline earth metal salts that can be converted to chloride salts during the oxychlorination process, such as other halide salts, such as nitrates, carbonates, sulfates, or bromides, may also be used. According to an embodiment, the at least one alkaline earth metal compound comprises a magnesium salt, such as magnesium chloride, magnesium nitrate, magnesium bromate, magnesium carbonate, or magnesium sulfate. In an embodiment, the at least one alkaline earth metal compound comprises magnesium chloride. The at least one alkaline earth metal may comprise magnesium as metal in an amount of about 0.5% to about 5.0%, or about 0.75% to about 4.0%, or about 1.0% to about 3.0%, by weight, based on the total weight of the catalyst composition, or any individual value or subrange within these ranges. According to an embodiment, the catalyst may comprise magnesium metal in an amount of less than about 5.0%, less than about 4.0%, less than about 3.0%, or any individual value or subrange within this range, based on the total weight of the catalyst composition. When an additional alkaline earth metal is included, the catalyst may comprise about 0.005% to about 10.0%, or any individual value or subrange within this range, of the additional alkaline earth metal.
[0039] The at least one transition metal compound comprises zirconium and may comprise additional transition metals, such as Sc, Tl, V, Y, Nb, La, Hf, Ta, Ac, Rf, Ha, Mn, or mixtures thereof. In one or more embodiments, the at least one transition metal compound comprises zirconium and is free of, or contains only trace amounts (e.g., less than 0.05 wt.%) of, other transition metals / compounds. In one or more embodiments, the catalyst composition comprises zirconium and does not comprise manganese (Mn) or rhenium (Re). The at least one transition metal compound may be used in the form of a water-soluble salt, such as a transition metal chloride (e.g., an oxychloride). However, other salts that can be converted to chloride salts during the oxychlorination process, such as other halide salts, such as nitrates, carbonates, sulfates, or bromides, may also be used. According to an embodiment, the at least one transition metal compound comprises a zirconium salt, such as zirconium chloride, zirconium oxychloride, zirconium chloride, zirconium carbonate, or zirconium hydroxide. These zirconium salts may contain other transition metals, such as Hf, as impurities at about 0.05% to about 1.0% by weight, or any individual value or subrange within this range. The at least one transition metal may contain zirconium as metal in a range of about 0.1% to about 3.0% by weight, or about 0.5% to about 2.0% by weight, or about 0.75% to about 1.0% by weight, based on the total weight of the catalyst composition, or any individual value or subrange within these ranges. According to an embodiment, the catalyst may contain zirconium metal in an amount of less than about 3.0% by weight, less than about 2.0% by weight, less than about 1.0% by weight, or any individual value or subrange within these ranges, based on the total weight of the catalyst composition. If an additional transition metal is included, the catalyst may contain about 0.005% to about 10.0% by weight of the additional transition metal, or any individual value or subrange within this range.
[0040] The final catalyst composition, which contains a copper compound, at least one alkaline earth metal compound including magnesium, and at least one transition metal compound including zirconium, can be easily fluidized. Other metals, such as rare earth metals and / or transition metals other than zirconium, can be present in the catalyst composition in relatively small or trace amounts. Typically, these metals, if present, are present in an amount less than about 0.05 wt. %, based on the total weight of the catalyst composition.
[0041] Preparation of the Catalyst Composition One method of loading metals (e.g., Cu, Mg, and Zr) onto an alumina support is accomplished by impregnating the support with an aqueous solution of a water-soluble salt of the metal, and then drying the wet support. The at least one alkaline earth metal, including magnesium, and at least one transition metal, including zirconium (and any additional metals) can be, but need not be, calcined on the support prior to depositing the copper compound to produce a fluidizable catalyst. According to an embodiment, a desired amount of metal salt is dissolved in water with vigorous stirring at a temperature of 60° C. After dissolution, the metal salt solution is slowly introduced onto the alumina support, for example, in a tumbler at 90 revolutions per minute. After impregnation, the wet catalyst can be dried in a drying oven heated to about 100° C. to about 180° C., or any individual value or subrange within this range, for about 2 hours to about 30 hours, or about 10 hours to about 28 hours, or about 20 hours to about 25 hours, or any individual value or subrange within this range. The dried catalyst can be hot sieved using a 500 μm sieve.
[0042] Certain properties, such as surface area and pore volume, can be modified through the deposition of metal salts. The catalyst compositions described herein have a surface area of about 20 to about 220 m 2 / g, or about 60 to about 180 m 2 / g, or about 70 to about 170 m 2 / g, or about 80m 2 / g~about 150m 2 / g, or about 150m 2 / g ~ approx. 215m 2 / g, or any individual value or subrange within these ranges.
[0043] According to an embodiment, the catalyst composition can be prepared by wetting the alumina support material with an aqueous solution of salts of the desired metals, as described above. The wetted alumina is then slowly dried at a temperature of about 75°C to about 180°C, about 90°C to about 200°C, about 100°C to about 180°C, or any individual value or subrange within these ranges, to remove the water. The amount of metal salt is selected so that the final catalyst contains about 1.0% to about 10% by weight copper, about 0.5% to about 5.0% by weight magnesium, and about 0.1% to about 3.0% by weight zirconium, or any individual value or subrange within these ranges. All metals are calculated based on the total weight of the catalyst composition, including the catalyst support, the metal, and any associated ligands or counter anions of the metal additives. The metal salts used in the aqueous solution can be in the form of any water-soluble salt as described above, such as chloride or oxychloride salts, or any salt known to those skilled in the art.
[0044] The salts used are typically copper chloride (CuCl2*2H2O), magnesium chloride (MgCl2*6H2O), and zirconium oxychloride (ZrOCl2*8H2O). These salts are weighed and then dissolved in deionized water at 60° C. with stirring (for example, using an impeller at about 100 rpm). The carrier used is approximately 50 ml 2 / g ~ approx. 250m 2 / g, or about 70m 2 / g ~ approx. 225m 2 / g, or about 100m 2 / g ~ approx. 215m 2 / g, or about 150m 2 / g ~ approx. 205m 2 Surface area per gram: 0.3 to approx. 0.6 cm 3The support can be a gamma alumina powder having a pore volume of about 10 μm to about 115 μm, or about 20 μm to about 110 μm, or about 25 μm to about 100 μm, or about 30 μm to about 80 μm, or any individual value or subrange within these ranges. The support is transferred to a baffled vessel or tumbler rotated at about 90 revolutions per minute. The salt solution is dripped onto the support within 30 minutes.
[0045] After impregnation, the wet catalyst can be dried in an oven at a temperature of about 100° C. to about 200° C. for about 1 hour to about 10 hours, for example, the wet catalyst can be dried at 100° C. for about 4 hours, at 110° C. for 16 hours, at 130° C. for 2 hours, at 150° C. for 2 hours, and at 180° C. for 4 hours, or any individual value or subrange within these ranges. The dried catalyst can be hot sieved at a temperature of about 100° C. to about 200° C., for example at a temperature of 130° C., using a 500 μm sieve, or a 475 μm sieve, or a 450 μm sieve, or a 400 μm sieve, or a 350 μm sieve, or a 300 μm sieve, or any individual value or subrange within these ranges.
[0046] Methods of using the catalyst composition Also described herein is a process for using the catalyst composition described herein for the oxychlorination of ethylene to form DCE. The process comprises contacting ethylene, oxygen or an oxygen-containing gas, and hydrogen chloride (HCl) in a reaction zone with the catalyst composition described herein, and recovering the effluent of the reaction zone. The catalyst employed comprises at least one alkaline earth metal, including copper, magnesium, and at least one transition metal, including zirconium. The metals are deposited on a high surface area support for fluidized bed application.
[0047] When the catalyst composition is initially charged or recharged into the oxychlorination reactor prior to DCE production, the catalyst bed is generally first heated and fluidized with air, oxygen-enriched air, or nitrogen-enriched air (when operated as a once-through process) before dosing with ethylene. In processes where vent gas is recycled to the reactor, either nitrogen, a mixture of oxygen and nitrogen, or a mixture containing nitrogen, oxygen and carbon dioxide can be used.
[0048] The catalyst compositions described herein can be operated above the optimum operating temperature of the comparative composition. However, to take advantage of the ability to produce higher crude purity DCE with sufficient ethylene efficiency, the catalyst composition should be operated at a lower operating temperature relative to the comparative composition. The catalyst compositions described herein can be operated at temperatures from about 0° C. to about 15° C., or from about 2° C. to about 10° C., or from about 3° C. to about 7° C. lower than the comparative composition. Surprisingly, higher crude DCE purity is achieved while operating at lower temperatures without loss of HCl and ethylene conversion or loss of flowability due to catalyst sticking.
[0049] The catalyst composition described herein is a highly efficient catalyst for the oxychlorination of ethylene to DCE. The reaction process temperature can vary from about 180°C to about 260°C, or from about 210°C to about 250°C. The reaction pressure can vary from about atmospheric pressure to about 200 psig. The contact time (defined as the ratio of the reactor volume taken up by the catalyst to the volumetric flow rate of the feed gas at the reactor control temperature and maximum pressure) in the fluidized bed catalyst and the fixed bed catalyst can vary from about 10 seconds to about 50 seconds, and can be from about 20 seconds to about 35 seconds. The ratio of ethylene, HCl and oxygen reactants based on moles of HCl fed to the reactor can range from about 1.0 mole to about 2.0 moles of ethylene and about 0.5 moles to about 0.9 moles of oxygen per 2.0 moles of HCl. A typical oxychlorination process is intended to operate within a stoichiometric ratio range of about 1 mole to about 2 moles of HCl to 1 mole of ethylene. EXAMPLES
[0050] The following examples are provided to illustrate the unique and unexpected properties of the catalyst compositions and methods described herein, but are not intended to limit the invention. The examples particularly point out the critical conditions of the embodiment using a combination of copper chloride, at least one alkaline earth metal, including magnesium, and at least one transition metal, including zirconium. In all examples, the fluidized bed oxychlorination reaction is carried out using a laboratory-scale fluidized bed reactor. The reactor volume, amount of catalyst charged to the reactor, fluid density, reactant flow rate, temperature, and pressure all affect the contact time of the reactants with the catalyst. The height-to-diameter ratio of the reactor also affects reaction conversion, selectivity, and efficiency. Therefore, all catalyst performance evaluations are carried out in substantially the same laboratory-scale reactor, using the same reaction contact time, the same feed conditions, and the same reactor control method, to ensure that differences in catalyst performance measurements are due to differences in the inherent properties of the catalyst, rather than differences in reactor geometry or reactor conditions. The reactor is equipped with means for supplying gaseous ethylene, oxygen, nitrogen, and HCl to the reactor zone, means for controlling the amounts of reactants and reaction conditions, and means for measuring and verifying the composition of the effluent gases to determine percent HCl conversion, percent DCE yield, percent ethylene efficiency, and purity of the DCE product.
[0051] Reactor Description A tubular glass reactor with an internal diameter of 2 cm was used to test the catalytic performance. The reactor was operated at 4 bar and was loaded with catalyst to give a fluidized bed height of approximately 115 cm. The feed gas consisted of 45.5 NL / h N2, 14.95 NL / h ethylene, 28.40 NL / h HC1, and 10.15 NL / h O2, with molar ratios of HCl / ethylene, O2 / HCl, and O2 / ethylene of 1.9, 0.35, and 0.68, respectively. The reaction temperature was measured by a central thermocouple in the fluidized bed and was regulated by external electrical heating. The reaction temperature can vary within a wide range and is typically between 215 and 240 °C. Hydrochloric acid in the feed and product gases was measured by titration, and N2, ethylene, O2, CO, and chlorinated hydrocarbons were analyzed by gas chromatography (GC). Based on the analytical results and the feed gas volume, the HCl conversion, ethylene conversion, DCE selectivity, and selectivity to various oxidation and chlorination by-products were calculated. Chemical performance was evaluated at temperatures above 215°C where the HCl conversion was typically above 97%. Sticking resistance was evaluated by gradually lowering the temperature to 195°C or the point where the pressure drop across the fluidized bed reached 100 mbar. Under typical fluidized or non-sticky conditions, the catalyst moved freely and smoothly through the reactor, the exit velocity of the effluent gas was fairly constant, and any gaseous pockets or bubbles observed in the bed were small in diameter and negligible in quantity. This visual observation corresponds to the differential pressure measurements observed under good fluidized or non-sticky conditions, where the differential pressure values contained little noise or fluctuation. Under non-sticky operating conditions, a typical pressure drop of about 78±2 mbar was observed. All catalysts were tested under the same conditions so that the results could be directly compared.
[0052] Example 1 The catalyst was prepared by impregnating an alumina support (Catalox® SCCa-25 / 200) manufactured by Sassol with an aqueous solution of metal chlorides, prepared by dissolving copper chloride (CuCl2·2H2O), magnesium chloride (MgCl2·6H2O), potassium chloride (KCl2·2H2O), and zirconium oxychloride (ZrOCl2·8H2O) in water at 60 °C under vigorous stirring. The supports used had a surface area of 180–200 m2. 2 / g and the pore volume is 0.4-0.5 cm3 / g, with a particle size distribution of about 20 μm to about 100 μm (about 4.0% of the particles are smaller than 22 μm, about 10% of the particles are smaller than 31 μm, about 29% of the particles are smaller than 44 μm, about 85% of the particles are smaller than 88 μm, and about 98% of the particles are smaller than 125 μm). Furthermore, the support material contains about 0.1 to 0.2% Ti expressed in metallic form as an impurity from the manufacturing process. The metal composition of the prepared catalyst was 4.5% by mass Cu, 1.9% by mass Mg, 0.25% by mass K, and 1.0% by mass Zr.
[0053] Example 2 Catalox® SCCa-25 / 200 was impregnated with metal chlorides such as Cu, Mg, and Zr using the same raw materials as in Example 1. The metal composition was 4.5% by weight Cu, 2.0% by weight Mg, and 1.0% by weight Zr.
[0054] Example 3 Metal chlorides were impregnated into Catalox® SCCa-25 / 200. The metal composition was 4.5 wt% Cu, 1.6 wt% Mg, and 1.0 wt% Zr.
[0055] Example 4 Metal chlorides were impregnated into Catalox® SCCa-25 / 200. The metal composition was 4.5 wt% Cu, 1.0 wt% Mg, and 1.0 wt% Zr.
[0056] Example 5 Metal chlorides were impregnated into Catalox® SCCa-25 / 200. The metal composition was 4.5 wt% Cu, 1.3 wt% Mg, and 1.0 wt% Zr.
[0057] Comparative Example 1 Metal chlorides were impregnated into Catalox® SCCa-25 / 200. The metal composition was 4.15 wt% Cu and 2.12 wt% Mg.
[0058] Comparative Example 2 Metal chlorides were impregnated into Catalox® SCCa-25 / 200. The metal composition was 4.3 wt% Cu, 1.3 wt% Mg, 1.0 wt% Mn, and 1.0 wt% K.
[0059] Comparative Example 3 A catalyst was prepared similarly to Example 1, except that the Zr content in the metal chloride solution was omitted. The metal composition was 4.5 wt% Cu, 1.9 wt% Mg, and 0.25 wt% K.
[0060] Comparative Example 4 A catalyst was prepared similarly to Example 5, except that the Zr content in the metal chloride solution was omitted. The metal composition was 4.5 wt% Cu and 1.3 wt% Mg.
[0061] [Table 1]
[0062] The catalytic performance of all the inventive examples and comparative examples was measured at 220-240°C and plotted in Figures 1-5. In Figure 1, by comparing Example 1 and Comparative Example 3, it was revealed that the DCE selectivity (ethylene conversion rate) was improved by adding 1.0 mass% Zr to the catalyst composition, but the activity of Example 1 was similar to that of Comparative Example 3 (Figures 4 and 5). As shown in Figure 2, the improvement in DCE purity of Example 1 is mainly due to, but not limited to, the decrease in selectivity to chlorinated by-products. As a result, the purity of the DCE product of Example 1 was about 0.2 percentage points higher than that of Comparative Example 3 throughout the overall ethylene conversion rate (Figure 2).
[0063] The purity of the DCE product (ethylene conversion) can also be improved by changing the Mg content in the catalyst composition, for example by reducing the Mg content from 1.9% by mass to 1.0% by mass (Examples 2 to 5 in FIG. 2). However, in this case, the improvement in DCE purity (ethylene conversion) is mainly due to the improvement in catalyst activity at lower operating temperatures (below 230° C.) where the selectivity to chlorinated by-products decreases.
[0064] The effect of Zr compounds on the selectivity to chlorinated by-products and therefore on the DCE purity was reaffirmed when comparing the catalytic performance of Comparative Example 4 and Example 5, which have the same catalytic formulation as Example 5 except for the Zr content. Both samples show similar catalytic activity, but the DCE purity of Example 5 is about 0.1-0.2 percentage points higher than that of Comparative Example 4, as shown above in the comparison of Example 1 and Comparative Example 3. As a result, the Zr content is considered to be a promoter that can improve the purity of the DCE product in the oxychlorination of ethylene to 1,2-dichloroethane without adjusting the catalytic activity.
[0065] Furthermore, the examples of the present invention introduced above show superior DCE purity compared to Comparative Example 1 and Comparative Example 2.
[0066] The activity test of the corresponding catalysts by decreasing the reaction temperature by 2°C or 3°C / step followed by the stickiness test revealed that the examples of the present invention exhibit sufficient fluidity up to 195°C under the reaction conditions, which indicates that some of the examples of the present invention are applicable to commercial plants operating at less than 230°C.
[0067] The foregoing description provides numerous specific details, such as examples of specific systems, components, methods, and the like, to provide a thorough understanding of some embodiments of the present invention. However, it will be apparent to one of ordinary skill in the art that at least some embodiments of the present invention can be practiced without these specific details. In other instances, well-known components or methods have not been described in detail to avoid unnecessarily obscuring the present invention. Thus, the specific details described are illustrative. It is contemplated that certain embodiments may vary from these illustrative details and still be within the scope of the present invention.
[0068] Although the operations of the methods herein are described in a particular order, the order of operations of each method may be changed such that certain operations are performed in the reverse order, or that certain operations are performed at least in part concurrently with other operations. In alternative embodiments, instructions of separate operations or sub-operations may be performed in an intermittent and / or alternating manner.
[0069] It should be understood that the above description is intended to be illustrative, and not restrictive. Many other embodiments will be apparent to those of ordinary skill in the art upon reading and understanding the above description. The scope of the invention should, therefore, be determined with reference to the appended claims, along with the full scope of equivalents to which such claims are entitled.
Claims
1. A carrier, and The catalytic metal compound on the support A catalyst composition comprising: the catalytic metal compound comprises a copper compound and a zirconium compound; The carrier is about 50 m 2 / g ~ approx. 250m 2 / g BET surface area of the catalyst composition.
2. The catalyst composition of claim 1 , wherein the support comprises alumina.
3. 3. The catalyst composition of claim 1 or 2, wherein the support comprises gamma alumina.
4. 3. The catalyst composition of claim 1 or 2, wherein the catalytic metal compound is impregnated on the support.
5. 3. The catalyst composition of claim 1 or 2, wherein the catalytic metal compound is adsorbed on the support.
6. 3. The catalyst composition of claim 1 or 2, wherein the copper compound comprises a copper salt.
7. 7. The catalyst composition of claim 6, wherein the copper salt is selected from the group consisting of copper chloride, copper nitrate, copper bromate, copper carbonate, copper sulfate, and combinations thereof.
8. 3. The catalyst composition of claim 1 or 2, wherein the catalytic metal compounds further comprise at least one alkaline earth metal compound comprising magnesium.
9. 9. The catalyst composition of claim 8, wherein the at least one alkaline earth metal compound comprises a magnesium salt.
10. 10. The catalyst composition of claim 9, wherein the magnesium salt is selected from the group consisting of magnesium chloride, magnesium nitrate, magnesium bromate, magnesium carbonate, magnesium sulfate, and combinations thereof.
11. 3. The catalyst composition of claim 1 or 2, wherein the zirconium compound comprises a zirconium salt.
12. 12. The catalyst composition of claim 11, wherein the zirconium salt is selected from the group consisting of zirconium oxychloride, zirconium chloride, zirconium carbonate, zirconium nitrate, zirconium hydroxide, and combinations thereof.
13. 3. The catalyst composition of claim 1 or 2, comprising about 1.0 wt.% to about 10.0 wt.% copper metal, based on the total weight of the catalyst composition.
14. 3. The catalyst composition of claim 1 or 2, wherein the catalytic metal compound further comprises about 0.5 wt.% to about 5.0 wt.% magnesium metal, based on the total weight of the catalyst composition.
15. 3. The catalyst composition of claim 1 or 2 comprising about 0.1 wt.% to about 3.0 wt.% zirconium metal, based on the total weight of the catalyst composition.
16. 3. The catalyst composition of claim 1 or 2, wherein the catalyst composition has an ethylene dichloride selectivity of about 95 mole % to about 99.9 mole % when contacted with hydrochloric acid, ethylene and oxygen at a temperature of about 200° C. to about 250° C.
17. 3. The catalyst composition of claim 1 or 2, wherein the catalyst composition, when used in the oxychlorination of ethylene, provides a crude dichloroethane purity of from about 99.2% to about 99.9% by weight.
18. 3. The catalyst composition of claim 1 or 2, wherein the support comprises at least one of a plurality of particles, granules, spheres, tablets, or extrudates.
19. 3. The catalyst composition of claim 1 or 2, wherein the support has a particle size distribution in which: (a) about 90 to about 100 volume percent of the particles are less than about 150 μm; (b) about 50 to about 60 volume percent of the particles are less than about 75 μm; and (c) about 20 to about 35 volume percent of the particles are less than about 45 μm, the particle size distribution being measured by a Malvern Instruments laser diffraction analyzer at about 20° C. to about 25° C. and about 1 atm, where a 5 g sample of the support is dispersed in 100 mL of deionized water using a magnetic stirrer for 1 minute to form a suspension, and 4 mL of the suspension is diluted with 130 mL of deionized water and analyzed by the analyzer at 2500 rpm.
20. 3. The catalyst composition of claim 1 or 2, which is free of silica.
21. 3. The catalyst composition of claim 1 or 2, wherein the support is unactivated or the support does not comprise activated alumina.
22. A carrier, and The catalytic metal compound on the support A catalyst composition comprising: the catalytic metal compound comprises a copper compound and a zirconium compound; 1. A catalyst composition comprising: said support having a particle size distribution in which: (a) about 90 to about 100 volume percent of the particles are less than about 150 μm; (b) about 50 to about 60 volume percent of the particles are less than about 75 μm; and (c) about 20 to about 35 volume percent of the particles are less than about 45 μm, the particle size distribution being measured at about 20° C. to about 25° C. and about 1 atm by a Malvern Instruments laser diffraction analyzer, wherein a 5 g sample of said support is dispersed in 100 mL of deionized water using a magnetic stirrer for 1 minute to form a suspension, and 4 mL of the suspension is diluted with 130 mL of deionized water and analyzed using said analyzer at 2500 rpm.
23. 23. The catalyst composition of claim 22, wherein the support comprises alumina.
24. 24. The catalyst composition of claim 23, wherein the support comprises gamma alumina.
25. 24. The catalyst composition of claim 22 or 23, wherein the catalytic metal compound is impregnated on the support.
26. 24. The catalyst composition of claim 22 or 23, wherein the catalytic metal compound is adsorbed on the support.
27. 24. The catalyst composition of claim 22 or 23, wherein the copper compound comprises a copper salt.
28. 28. The catalyst composition of claim 27, wherein the copper salt is selected from the group consisting of copper chloride, copper nitrate, copper bromate, copper carbonate, copper sulfate, and combinations thereof.
29. 24. The catalyst composition of claim 22 or 23, wherein the catalytic metal compounds further comprise at least one alkaline earth metal compound comprising magnesium.
30. 30. The catalyst composition of claim 29, wherein the at least one alkaline earth metal compound comprises a magnesium salt.
31. 31. The catalyst composition of claim 30, wherein the magnesium salt is selected from the group consisting of magnesium chloride, magnesium nitrate, magnesium bromate, magnesium carbonate, magnesium sulfate, and combinations thereof.
32. 24. The catalyst composition of claim 22 or 23, wherein the zirconium compound comprises a zirconium salt.
33. 33. The catalyst composition of claim 32, wherein the zirconium salt is selected from the group consisting of zirconium oxychloride, zirconium chloride, zirconium carbonate, zirconium hydroxide, and combinations thereof.
34. 24. The catalyst composition of claim 22 or 23 comprising about 1.0 wt.% to about 10.0 wt.% copper metal, based on the total weight of the catalyst composition.
35. 24. The catalyst composition of claim 22 or 23, comprising about 0.5 wt.% to about 5.0 wt.% magnesium metal, based on the total weight of the catalyst composition.
36. 24. The catalyst composition of claim 22 or 23 comprising about 0.1 wt.% to about 3.0 wt.% zirconium metal, based on the total weight of the catalyst composition.
37. 24. The catalyst composition of claim 22 or 23, wherein the catalyst composition has an ethylene dichloride selectivity of about 95 mole % to about 99.9 mole % when contacted with hydrochloric acid, ethylene and oxygen at a temperature of about 200° C. to about 250° C.
38. 24. The catalyst composition of claim 22 or 23, wherein the catalyst composition, when used in the oxychlorination of ethylene, provides a crude dichloroethane purity of from about 99.20% to about 99.80% by weight.
39. 24. The catalyst composition of claim 22 or 23, wherein the support comprises at least one of a plurality of particles, granules, spheres, tablets, or extrudates.
40. 24. The catalyst composition of claim 22 or 23, which is free of silica.
41. 24. The catalyst composition of claim 22 or 23, wherein the support is unactivated or the support does not comprise activated alumina.
42. dissolving a copper compound and at least one compound comprising zirconium in a solvent with stirring at a temperature of about 20° C. to about 80° C. to form a solution; The solution is about 50 ml 2 / g ~ approx. 250m 2 / g BET surface area, said carrier being rotated at about 50 revolutions per minute (rpm) to about 150 rpm; drying the coated support at a temperature of about 75° C. to about 180° C. for about 1 hour to about 20 hours to remove free water to produce a catalyst composition; A method for producing a catalyst composition comprising:
43. 43. The method of claim 42, wherein the copper compound comprises a copper salt.
44. 44. The method of claim 43, wherein the copper salt is selected from the group consisting of copper chloride, copper nitrate, copper bromate, copper carbonate, copper sulfate, and combinations thereof.
45. 44. The method of claim 42 or 43, wherein the catalytic metal compound further comprises at least one alkaline earth metal compound comprising magnesium.
46. 43. The method of claim 42, wherein the magnesium compound comprises a magnesium salt.
47. 47. The method of claim 46, wherein the magnesium salt is selected from the group consisting of magnesium chloride, magnesium nitrate, magnesium bromate, magnesium carbonate, magnesium sulfate, and combinations thereof.
48. 44. The method of claim 42 or 43, wherein the zirconium compound comprises a zirconium salt.
49. 49. The method of claim 48, wherein the zirconium salt is selected from the group consisting of zirconium oxychloride, zirconium chloride, zirconium carbonate, zirconium hydroxide, and combinations thereof.
50. 44. The method of claim 42 or 43, wherein the solvent is selected from the group consisting of deionized water, alcohol, isopropyl alcohol, acetic acid, hydrochloric acid, mineral acids, nitric acid and sulfuric acid.
51. 44. The method of claim 42 or 43, wherein the support comprises alumina.
52. 44. The method of claim 42 or 43, wherein the support comprises gamma alumina.
53. 44. The method of claim 42 or 43, wherein the carrier comprises at least one of a plurality of particles, granules, spheres, tablets, or extrudates.
54. The method of claim 42 or 43, wherein the stirring comprises stirring at about 200 rpm to about 700 rpm.
55. 44. The method of claim 42 or 43, wherein the dissolving is carried out at a temperature of about 30°C to about 70°C.
56. 44. The method of claim 42 or 43, wherein administering the solution comprises adding the solution dropwise to a container containing the carrier.
57. 44. The method of claim 42 or 43, wherein the coated support comprises a copper compound, a magnesium compound and a zirconium compound impregnated therein or adsorbed thereon.
58. 44. The method of claim 42 or 43, wherein the carrier is in a tumbler during administration.
59. 44. The method of claim 42 or 43, wherein the support is rotated at about 1 revolution per 5 seconds to about 5 revolutions per 5 seconds.
60. 44. The method of claim 42 or 43, wherein the support has a particle size distribution in which (a) about 90 to about 100% by volume of the particles are less than about 150 μm; (b) about 50 to about 60% by volume of the particles are less than about 75 μm; and (c) about 20 to about 35% by volume of the particles are less than about 45 μm, the particle size distribution being measured by a Malvern Instruments laser diffraction analyzer at about 20° C. to about 25° C. and about 1 atm, wherein a 5 g sample of the support is dispersed in 100 mL of deionized water using a magnetic stirrer for 1 minute to form a suspension, and 4 mL of the suspension is diluted with 130 mL of deionized water and analyzed using the analyzer at 2500 rpm.
61. 44. The method of claim 42 or 43, wherein the catalyst composition is free of silica.
62. 44. The method of claim 42 or 43, wherein the support is not activated or the support does not comprise activated alumina.
63. Conversion of ethylene to dichloroethane using an oxychlorination process in the presence of a catalyst composition 3. A method of using the catalyst composition of claim 1 or 2, comprising:
64. 64. The process of claim 63, which when contacted with hydrochloric acid, ethylene and oxygen at a temperature of from about 200° C. to about 250° C. provides an ethylene dichloride selectivity of from about 95 mole percent to about 99.9 mole percent.
65. 64. The method of claim 63, which when used in an oxychlorination process provides a crude dichloroethane purity of from about 99.2% to about 99.9% by weight.